2018
DOI: 10.1186/s13071-018-3021-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of intestinal helminths of red foxes (Vulpes vulpes) in central Europe (Poland): a significant zoonotic threat

Abstract: BackgroundThe red fox (Vulpes vulpes) is widely distributed in the world; in central Europe, it is the most numerous wild species of the family Canidae. It can play the role of a definitive host for many intestinal parasites, including zoonotic helminths. Poland, with its geographical location (central Europe), is an interesting area for parasitological investigations of this species. The aim of this study was to evaluate and compare the prevalence of intestinal helminths in red foxes in different regions of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
51
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 42 publications
(99 reference statements)
11
51
0
5
Order By: Relevance
“…Polish foxes in the present study. Similar prevalence has been demonstrated in studies in northern and southern Poland (1,30). However, another studies conducted in western and southern Poland showed a significantly lower prevalence of these nematodes (11-35%) (31,32,33).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Polish foxes in the present study. Similar prevalence has been demonstrated in studies in northern and southern Poland (1,30). However, another studies conducted in western and southern Poland showed a significantly lower prevalence of these nematodes (11-35%) (31,32,33).…”
Section: Discussionsupporting
confidence: 84%
“…The exceptions are the studies from the Czech Republic, where the prevalence of both species in foxes was equal (2).The parasite with the lowest prevalence in this study was Trichuris vulpis. This was supported by the results of Karamon et al(1) in Poland, who reported foxes infected with this nematode from 1.3% in south-east Poland to 4.4% in the north of the country. High prevalence have been reported only in southern Poland (64.4%)(50).…”
supporting
confidence: 80%
See 2 more Smart Citations
“…Our prevalence of E. multilocularis is very similar to the 2.6% found in the bordering Slovenia in 2010 (15), but it is much lower than that recorded in endemic areas of Europe. There, E. multilocularis may reach in red foxes very high prevalence locally, such as 28.5% in Denmark (44), 25.6% in Poland (45), and in general a prevalence over 10% in eastern countries (reviewed in Oksanen (3)),…”
Section: Discussionmentioning
confidence: 99%